Shirley Temple and the Performance of Girlhood - Hatch, Kristen (Book collections on Project MUSE., 2014)
In the 1930's, Shirley Temple was heralded as "America's sweetheart," and she remains the icon of wholesome American girlhood, but Temple's films strike many modern viewers as perverse. Shirley Temple and the Performance of Girlhood examines her early career in the context of the history of girlhood and considers how Temple's star image emerged out of the Victorian cult of the child. Beginning her career in "Baby Burlesks," short films where she played vamps and harlots, her biggest hits were marketed as romances between Temple and her adult male costars. Kristen Hatch helps modern audiences.